EFFECTIVENESS OF FIVES STRATEGY IN TEACHING READING COMPREHENSION - Wiki Tedi Rahmawati; Yunita Mutiara Harahap; Ramlah Ramlah (Universitas Galuh, 2022)
This research was aimed to find the effectiveness of FIVES strategy in teaching reading comprehension. This research was conducted by applying experimental research design. The sample was two classes with total number of 60 students taken out of the total population by applying cluster random sampling technique. One class as the experimental group was taught by applying FIVES strategy and the other class as the control group was taught by conventional strategy. The instrument for collecting the data was reading text with 20 items of multiple choices test. The data were analyzed by using t-test formula. Data analysis resulted that t-observed value was higher than t-table value ( > 2.000) at level of significance 0.05 with the degree of freedom (df) 58. Since t-observed value was higher than t-table value, it means Ha was accepted and Ho was rejected. Thus, the FIVES strategy significantly affected students’ reading comprehension. It is recommended for English teachers to apply the FIVES strategy to teach reading comprehension.